Detection of magnetic field effects by confocal microscopy - Déjean, V; Konowalczyk, M; Gravell, J; Golesworthy, MJ; Gunn, C; Pompe, N; vander Elst, OF; Oxborrow, M; Aarts, DGAL; Mackenzie, S; Timmel, C (Royal Society of Chemistry, 2020)
Certain pairs of paramagnetic species generated under conservation of total spin angular momentum are known to undergo magnetosensitive processes. Two prominent examples of systems exhibiting these so-called magnetic field effects (MFEs) are photogenerated radical pairs created from either singlet or triplet molecular precursors, and pairs of triplet states generated by singlet fission. Here, we showcase confocal microscopy as a powerful technique for the investigation of such phenomena. We first characterise the instrument by studying the field-sensitive chemistry of two systems in solution: radical pairs formed in a cryptochrome protein and the flavin mononucleotide/hen egg-white lysozyme model system. We then extend these studies to single crystals. Firstly, we report temporally- and spatially-resolved MFEs in flavin-doped lysozyme single crystals. Anisotropic magnetic field effects are then reported in tetracene single crystals. Finally, we discuss the future applications of confocal microscopy for the study of magnetosensitive processes with a particular focus on the cryptochrome-based chemical compass believed to lie at the heart of animal magnetoreception.